The Quality of Local Government Financial Report - Marcus R. Maspaitella; Mona Permatasari Mokodompit (Global Financial Accounting Journal, 2022)
Purpose - This study aims to analyze the influence of human resource competence, regional financial accounting information system, use of information technology and government internal control systems on the quality of local government financial report at the Regional Financial and Asset Management Agency (BPKAD) of Manokwari Regency. Research Method - The research data was collected by giving questionnaires to the employees at BPKAD office of Manokwari regency who carry out tasks in the accounting and finance functions. The data was then analyzed using multiple linear regression analysis. Findings - The results showed only the government internal control system factor that have influence on the quality of local government financial reports of BPKAD of Manokwari regency. Implication - This study provides information that can be used as a consideration in making policies in order to improve the quality of locel government financial report by the local government in Manokwari Regency, particulary BPKAD.